The Activities as a means of self-development for the education in values. Case: dance (salsacasino) (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2011)
The purpose of this research was to identify the facilitators of the DAC in the need to incorporateactivitiesinself-developmentstrategies that contribute to education invalues, emphasizing the roleof dance (SalsaCasino) as the idealfor this purpose.The researchis exploratory and descriptive.Thesample consisted of facilitators of self-belonging to the artistic and culturalsub-area (as the coordination of activitiesof self-developmentwithin the Department ofBasic Studies). To makethis consultation designinga questionnaire was developedbased onclosed questions andmeasured bya Likert scale. Its construction was taken as avariable of study, education invalues, and asindicators of thisvariable,institutional values selected by the researcher within thevalue system of UCLA.The results showed that the facilitators of theself-development activities that are held at theDAC/ UCLA believe that it is necessary to include estrategies for education invalues in the same and Dance (SalsaCasino) represents an ideal medium for the transmission ofvalues.This isthe first step forfurther researchtodevelopa teaching unitfor usein the activity of self Salsa Casino of the Dean of Business Administration and Accounting(DAC) of the University Lisandro Alvarado (UCLA).
Keywords: education in values; self-development activities; dance (salsacasino)